MEMODELKAN KEMISKINAN PENDUDUK PROVINSI BALI DENGAN REGRESI DATA PANEL - BUDINIRMALA, KADEK; SUCIPTAWATI, NI LUH PUTU; JAYANEGARA, KETUT; KENCANA, I PUTU EKA NILA (E-Jurnal Matematika, 2018)
One indicator of the success of development programs undertaken is the declining percentage of the poor, defined as the ratio of the number of people classified as poor to the total population. For Bali province, despite its economic growth is higher than national rate; 6.03 percent and 6.24 percent compared to 4.88 percent and 5.02 percent in 2015 and 2016, respectively; the poor are still observed in this province by 4.15 percent of its 4.2 million population in September 2016. In order to make development programs in Bali more effective to decrease the number of poor people, significant determinants of poor have to be recognised. The purpose of this work is to model and to determine the significant factor(s) that affect the percentage of poor in Bali province by applying panel data analysis. Percentage of poor for period 2007 to 2015 is positioned as the dependent variable while economic growth, unemployment rate, labor force participation rates, total population, and human development index as the independent ones. We found the best model to describe the causal relationship among variables is fixed effect model and two predictors, the economic growth rate and human development index, were significant in affecting the number of poor in Bali province.